Communication: Imaging wavefunctions in dissociative photoionization - Hopkins, W; Mackenzie, S (AIP Publishing, 2011)
The dissociative ionization dynamics of excited electronic states of the xenon dimer, Xe2, have been studied using velocity map ion imaging (VMI). A one-colour, (2+1) resonant excitation scheme was employed to first excite and then ionize selected vibrational levels of the Xe2 6p 2[1/2]0 0+g Rydberg state. Cationic fragments were then detected by the VMI. The data provide an outstanding example of the reflection principle in photodissociation with the full nodal structure of the Rydberg state wavefunctions clearly observed in the final Xe+ kinetic energy distributions without the need for scanning the excitation energy. Fitting of the observed distributions provides detailed and precise information on the form of the Xe2+ I(1/2g) potential energy curve involved which is in excellent agreement with the results of photoelectron imaging studies [Shubert and Pratt, J. Chem. Phys. 134, 044315 (2011) ]. Furthermore, the anisotropy of the product angular distributions yields information on the evolution of the electronic character of the ionic state with internuclear separation, R. The combination of the nature of dissociative ionization and the extent of the bound state wavefunctions provide information over an unusually wide range of internuclear separation R (ΔR > 0.75 Å). This would normally require scanning over a considerable energy region but is obtained in these studies at a fixed excitation energy.